1988
DOI: 10.1055/s-2007-1010868
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Muscular Ketone Extraction by Lipid Infusion in Man

Abstract: Using the forearm technique, muscular ketone body metabolism was investigated in 12 healthy volunteers during an i.v. infusion of lipid emulsions containing long chain triglycerides (LCT) or a mixture of medium- and long chain triglycerides (MCT/LCT). During the basal period, arterial concentrations and muscular extraction of beta-hydroxybutyrate and acetoacetate were linearly correlated as expected. This relationship was abolished during the infusion of both lipid emulsions. In addition, fractional extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With the lipid infusion, it is unclear whether these relationships are maintained, as one report by Rett et al. found that during a lipid infusion, peripheral extraction of ketones may dissociate from plasma concentrations 66 . Notably, these latter findings are not directly comparable to our data, as they utilized a lipid infusion protocol that produced much higher plasma FFAs (~1.90 vs. 0.88 mM) and lower concentrations of plasma βOHB (~0.45 vs. 0.78 mM), which may alter peripheral nutrient utilization.…”
Section: Discussionmentioning
confidence: 99%
“…With the lipid infusion, it is unclear whether these relationships are maintained, as one report by Rett et al. found that during a lipid infusion, peripheral extraction of ketones may dissociate from plasma concentrations 66 . Notably, these latter findings are not directly comparable to our data, as they utilized a lipid infusion protocol that produced much higher plasma FFAs (~1.90 vs. 0.88 mM) and lower concentrations of plasma βOHB (~0.45 vs. 0.78 mM), which may alter peripheral nutrient utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization also may be decreased during deficiency of insulin (Balasse and Havel, 1971) such as is seen in bovine ketosis. In addition, increased concentrations of NEFA and triglycerides decreased utilization of ketone bodies by skeletal muscle of humans (Rett et al, 1988). Future research should re-examine the role of ketone body utilization during early lactation and in the etiology of bovine ketosis.…”
Section: Lipidsmentioning
confidence: 97%